Between history and archaeology : papers in honour of Jacek Lech - Werra, Dagmara H.; Werra, Dagmara H.; Woźny, Marzena; Woźny, Marzena; Lech, Jacek (Archaeopress Publishing Ltd, 2018)
This is a collection of 46 papers papers in honour of Professor Jacek Lech, compiled in recognition of his research and academic career, as well as his inquiry into the study of prehistoric flint mining, Neolithic flint tools (and beyond), and the history of archaeology